Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1021/jp012473d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Characterization of Viologen-Functionalized Poly(Amidoamine) Dendrimers

Abstract: We report the preparation and characterization of viologen-functionalized generation 2, 4, and 6 poly-(amidoamine) (PAMAM) dendrimers. An amidation reaction between the succinimide ester of 1-ethyl-1′-(3-propionic acid)-4,4′-bipyridylium dibromide and the dendrimer primary amines resulted in 13-34% end group functionalization. The water-soluble dendrimers were examined by 1 H NMR, MALDI-TOF MS, and UV-vis spectroscopy to determine the extent of functionalization. UV-vis spectra, obtained following chemical red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…The PAMAM dendrimer generated a peak centered at 14,215 amu. As recently observed by Baker et al [35], a series of peaks at lower m/z were found in mass spectra for both molecules. They seem to be generated by fragmentation of the molecules during ionization, based on the observation that a mass peak of around 27,500 amu can be derived from the EO 3 -dendrimer.…”
Section: Synthesis and Characterization Of The Eo 3 -Dendrimersupporting
confidence: 83%
“…The PAMAM dendrimer generated a peak centered at 14,215 amu. As recently observed by Baker et al [35], a series of peaks at lower m/z were found in mass spectra for both molecules. They seem to be generated by fragmentation of the molecules during ionization, based on the observation that a mass peak of around 27,500 amu can be derived from the EO 3 -dendrimer.…”
Section: Synthesis and Characterization Of The Eo 3 -Dendrimersupporting
confidence: 83%
“…The MALDI-MS of PPI-Im 64 (Figure 2b) is a broad ill-defined peak typical of highgeneration dendrimers. 19,20 The inset shows the complete spectrum, which displays peaks at lower m/z, which are likely due to fragmentation of the dendrimer. The center of mass of the peak at 12,565 m/z is very close to the molecular mass (12,584) of a fully functionalized dendrimer in which the original dendritic starting material was missing 4 branches.…”
Section: Resultsmentioning
confidence: 99%
“…However, we view this possibility as unlikely because all experiments were carried out in solutions containing 0.1 M salt, which is a condition known to reduce the likelihood of dendrimer aggregation. 19 An alternative explanation for the low observed catalytic activity, is that the pK a of the imidazole units attached to dendrimers is outside the range of pH 5-9. However, it seems unlikely that the dendrimer attachment chemistry would result in a shift of more than one pH unit away from the pK a of monomeric imidazole (~7).…”
Section: Discussionmentioning
confidence: 99%
“…68 Electrochemical experiments performed on the two types of dendrimers in argonpurged MeCN solutions have revealed that in all cases only a fraction of the viologen units can be reduced, in agreement with previous results obtained for viologen groups appended at the periphery of poly(amido amine) dendrimers. 69 Within experimental error, this fraction corresponds to the number of the viologen units present in the outer shell (6 for A9 18 þ and B9 18 þ , and 12 for A21 42 þ and B21 42 þ ). The fact that the number of reducible viologen units is smaller than that expected cannot be attributed to lack of branches in the structures of the dendrimers because the 1 H NMR spectroscopic and mass spectral characterization show clearly that the compounds 6.5 VIOLOGEN-BASED DENDRIMERS Figure 6.18 Structural formulas of two families of dendrimers containing a 1,3,5-trisubstituted benzenoide core and 9 (A9 18 þ and B9 18 þ ) and 21 (B21 42 þ and A21 42 þ ) 4,4 0 -bipyridinium units in their branches.…”
Section: Viologen-based Dendrimersmentioning
confidence: 99%